2016
DOI: 10.1016/j.ijpddr.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the macrofilaricidal effects of flubendazole on adult female Brugia malayi using RNAseq

Abstract: The use of microfilaricidal drugs for the control of onchocerciasis and lymphatic filariasis (LF) necessitates prolonged yearly dosing. Prospects for elimination or eradication of these diseases would be enhanced by the availability of a macrofilaricidal drug. Flubendazole (FLBZ), a benzimidazole anthelmintic, is an appealing candidate. FLBZ has demonstrated potent macrofilaricidal effects in a number of experimental rodent models and in one human trial. Unfortunately, FLBZ was deemed unsatisfactory for use in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 78 publications
1
15
0
Order By: Relevance
“…However, no differences were found when we compared the gene expression levels of different beta-tubulin isotypes from treated and untreated worms. This has been observed previously in the filaroid nematode Brugia malayi after FLBZ exposure [ 53 ]. Although it has been shown that certain mutations are implicated in BZ resistance in strongylid nematodes [ 21 , 22 , 52 ], further investigation is required to confirm whether a similar mechanism is involved in the drug binding and selection for AR in ascarids, including A .…”
Section: Discussionsupporting
confidence: 80%
“…However, no differences were found when we compared the gene expression levels of different beta-tubulin isotypes from treated and untreated worms. This has been observed previously in the filaroid nematode Brugia malayi after FLBZ exposure [ 53 ]. Although it has been shown that certain mutations are implicated in BZ resistance in strongylid nematodes [ 21 , 22 , 52 ], further investigation is required to confirm whether a similar mechanism is involved in the drug binding and selection for AR in ascarids, including A .…”
Section: Discussionsupporting
confidence: 80%
“…D-dopachrome tautomerase (DDT) as a co-factor of macrophage inhibitory factor (MIF-1) [Merk et al, 2011] and reproductive timing, nurf-1 [Large et al, 2016]. We also identified signals consistent with local adaptation at a GABA transporter previously noted as being upregulated in studies of the anthelmintic flubendazole [Jiang et al, 2005, Mullen et al, 2006, Casida and Durkin, 2013, O'Neill et al, 2016. Only two regions, with a single known gene annotation, were consistent with adaptation in the Kenyan Wb population: the SLO-1 gene is a calcium-activated potassium channel [Welz et al, 2011].…”
Section: Most Recent Common Ancestor Supports a Southeast Asia Originmentioning
confidence: 63%
“…Four of the outlier genes have also been identified as potential targets for new anti-parasite drugs in the Malian and Kenyan populations of Wb: Na/Cl GABA transporter [Jiang et al, 2005, Mullen et al, 2006, Casida and Durkin, 2013, O'Neill et al, 2016, PAN domain protein [Kumar et al, 2007, O'Neill et al, 2016, SLO-1 Ca-activated K channel [Welz et al, 2011], phosphatidate cytidylyltransferase [Narayan et al, 1989, Crowther et al, 2010 (table 2). All of our samples were collected prior to mass drug administration; thus, the signal of local adaptation may be in response to other environmental factors rather than widespread drug resistance.…”
Section: Locally Adapted Haplotypes May Affect Future Drug Effectivenessmentioning
confidence: 99%
“…Our study showed that, similar to IKK inhibitors, flubendazole also suppressed NF-κB p65 phosphorylation by inhibiting IKK activation (Figure 4). Although several different mechanisms, such as specifically binding to tubulin,31 dysregulating cuticle-associated genes’ expression,32 and oxidative damage,33 have been reported for the anthelmintic action of flubendazole, it is still not clear how flubendazole affects IKK activation.…”
Section: Discussionmentioning
confidence: 99%